Local mobility culture as injunctive normative beliefs – A theoretical approach and a related measurement instrument. (October 2020) - Bamberg, Sebastian; Rollin, Philipp; Schulte, Maxie
Abstract: Local mobility culture is introduced as a theoretical concept that is useful for transformative research. This article conceptualizes local mobility culture as injunctive normative beliefs that comprise the priorities of a local transport system. The concept suggests that these beliefs are acquired through communication within social networks. The presented measure for local mobility culture proposes a structure of seven first-order factors reflecting the impact of two latent second-order factors. These indicate the perceived general social support for a more car-oriented vs. multimodality promoting local mobility culture. The results of three survey studies (N = 173, N = 610, N = 725) support the proposed measurement structure. Furthermore, the results also support the predictive validity of the new measure: Dimensions of local mobility culture have a substantive direct as well as indirect association with self-reported means of transport use, mediated by descriptive normative beliefs. Additionally, results indicate a substantive association between the perceived local mobility culture and objective characteristics of the local transport system. Implication of the results for research and transformative policy initiatives are discussed. Highlights: Mobility culture is introduces as a transformative theoretical concept. Mobility culture is theoretically conceptualized as injunctive normative beliefs. Mobility culture indicates social support for promoting car-use vs. multimodality. Mobility culture is a strong direct and indirect car use predictor.